Petrology of Oligocene Lalehzar igneous rocks in the southeast of Saveh-Naein-Jiroft magmatic belt - Fatemeh Sepidbar; Bahareh Borouzi Niyat (Journal of Economic Geology)
Lalehzar igneous rocks are located in the southeast of Iran, the SE of Saveh-Naein-Jiroft magmatic belt. In this study, zircon U-Pb dating, and whole-rock geochemistry and Sr-Nd isotopic analyzes were performed on granitoid rocks (granite and granodiorite) and associated volcanics. The granodiorites and granite include quartz, plagioclase, alkali feldspar, biotite and amphibole with different percentages. New zircon U–Pb ages show granitic magmatism at ~28 Ma, followed by emplacement of granodiorite at ~24 Ma. Both granitoid and volcanic rocks are characterized with depletion in Nb and Ti and enrichement in large ion lithophile (LILE) and light rare earth elements (LREE). Their calc-alkaline arc geochemical signature (low Sr/Y ratio of almost <55), negative to positive Eu anomalies (Eu/Eu∗⁠ =0.6–1.3) and the negative to positive εNd (t) values of -1.4 to +0.27 offer formations in an orogenic belt. The geochemistry and isotopic results show that they are formed during partial melting of the lower crust (amphibolite) which is impelemented by inherited mantle source components in a subduction zone.